HF radar for wind waves measurements in the Malta-Sicily Channel. (November 2018) - Orasi, Arianna; Picone, Marco; Drago, Aldo; Capodici, Fulvio; Gauci, Adam; Nardone, Gabriele; Inghilesi, Roberto; Azzopardi, Joel; Galea, Anthony; Ciraolo, Giuseppe; Sánchez Musulin, Jorge; Alonso-Martirena, Andres
Highlights: CODAR HF radar data can correctly describe sea wave conditions in quasi real-time. The study suggests the use of wave radar values registered at intermediate rings. At 13.5 MHz the threshold of 7.5 m to measure extreme wave heights is not strict. Radar data are useful to calibrate numerical models or to improve the model skill. Abstract: The CALYPSO HF radar network is a permanent and fully operational observing system currently composed of four CODAR SeaSonde stations. The system is providing real-time hourly maps of sea surface currents and waves data in the Malta-Sicily Channel. The present work aims to compare significant wave height measurements by HF Radar to wave data from numerical models and satellite altimeter. This is the first time that this set of wave data are analysed since the four HF radars were installed between 2012 and 2015. Results suggest that CODAR HF Radar wave data are a reliable source of wave information even in the case of extreme events, providing an avenue to improve and complete the offer of services deriving from the CALYPSO system. Comparisons of HF radar data with both numerical sea wave model and satellite altimeter data confirm agreement, in particular for radar measurements in the annular sectors within the central range-cells which are also characterized by a more reliable and homogeneous temporal behaviour.